Peran Motivasi Kerja Pada Karyawan Perusahaan Perbankan - Putri Meliana Santoso; Mochammad Isa Anshori (JURNAL RISET MANAJEMEN (JURMA), 2024)
This study aims to determine the role of motivation, factors, and impact on the performance of banking company employees. The method used in this study is a descriptive qualitative research method. In this study, it was used to collect information data through interviews with informants. The results of this study show that motivation has an important role that affects the performance of banking company employees.